Contribution of Songket Weaving Housewives in Improving Family Welfare in Silungkang Oso Village - Viona, Viona; Natsir, MHD (Universitas Negeri Padang, 2024)
This research is motivated by the involvement/participation of housewives who work as weaving craftsmen which have an impact on binding family welfare in the village of Silungkang Oso. This study aims to (1) describe the contribution of housewives in terms of (action terms) involvement and participation in improving family welfare in the village of Silungkang Oso (2) describe the contribution of housewives from (material aspect) financial donations/assistance in improving family welfare in village of Silungkang Oso. This type of research is a quantitative descriptive research. The population in this study were 80 housewives of songket weaving craftsmen who lived in Silungakng oso village. The sampling technique is simple random sampling of 40 people. Data collection techniques using a questionnaire. While the data collection tool is a questionnaire. The data analysis technique uses percentages. The results of the research on the contribution of housewives of songket weaving craftsmen in improving family welfare in Silungkang oso village in terms of (1) the involvement/participation of respondents who answered the questionnaire answered more questions, this always indicates the contribution of housewives in improving welfare family is quite high can be seen from the answers of respondents. (2) donations/funding. Respondents who answered the questionnaire answered more questions. This indicated that the contribution of housewives in improving family welfare was quite high, which could be seen from the respondents' answers.